Heterogeneity in Parent‐reported Social Skill Development in Early Elementary School Children. Issue 2 (2nd April 2013) - Lamont, Andrea; Van Horn, M. Lee
Abstract: Despite known risks associated with aberrant social skill development, there has been a relative dearth of literature on typical developmental changes in social skills over time. In this study, we examine systematic changes in social skills from kindergarten (typical age of 5–6 years) to third grade (typical age of 8–9 years), and focus on systematic heterogeneity across these developmental trajectories. Data came from the National Head Start—Public School Early Childhood Transition Demonstration Project (N = 6964). Mixture models provide evidence for multiple classes of individuals representing heterogeneity in the development of social skills. Classes were defined as a majority class (whose trajectories remained relatively stable over time), an increasing class (whose trajectories increased at a faster rate than the majority class), and a decreasing class (whose trajectories decreased at a faster rate than the majority class). Developmental trends accounted for a substantial proportion of the variance in social skill components. Implications and limitations of the study are discussed.